Research on Enterprise Marketing Strategies from the Perspective of New Media: Taking Goodme Company as an Example - Liu, Xiaokai (International Journal of Global Economics and Management, 2024)
New media has brought tremendous impact to traditional business models, and how enterprises can determine effective new media marketing strategies based on their product characteristics and market development direction has become a practical problem that enterprises need to solve at present. In this context, this paper takes Goodme Company as an example, conducts research and analysis on the company’s new media marketing situation, explores the characteristics and existing problems of the company’s new media marketing, and proposes highly targeted and actionable countermeasures, in order to provide reference for enterprises to formulate sound new media marketing strategies.